2016
DOI: 10.1111/codi.13281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a low Hartmann's procedure with low colorectal anastomosis with and without defunctioning ileostomy after radiotherapy for rectal cancer: results from a national registry

Abstract: LHP and LA with DI were associated with fewer infective complications and reoperations than LA alone. The rate of any complication was less after LHR than LA with or without DI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 30 publications
5
26
0
1
Order By: Relevance
“…The Dutch group also recently reported that, in patients with rectal cancer selected for RT, low HP was associated with a lower rate of infectious abdominal complications compared with low anterior resection (AR). In that study, 31% of the patients with rectal cancer were excluded because they had T4 tumours, underwent emergency surgery, did not have RT or had missing values [ 14 ]. However, only emergency procedures were excluded in the present study, and the rate of intra-abdominal infection was still low.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch group also recently reported that, in patients with rectal cancer selected for RT, low HP was associated with a lower rate of infectious abdominal complications compared with low anterior resection (AR). In that study, 31% of the patients with rectal cancer were excluded because they had T4 tumours, underwent emergency surgery, did not have RT or had missing values [ 14 ]. However, only emergency procedures were excluded in the present study, and the rate of intra-abdominal infection was still low.…”
Section: Discussionmentioning
confidence: 99%
“…In some of these patients, although sphincter preservation was technically possible, an abdominoperineal resection or low Hartmann's procedure with a permanent colostomy should be considered, as these procedures have a lower risk of postoperative complications. Colostomy would be more beneficial than a permanent ileostomy [21,[32][33][34]. When discussing the treatment plan, we need to ensure that the patient understands all the possible consequences of a diverting stoma.…”
Section: Discussionmentioning
confidence: 99%
“…Colostomy itself would be more bene cial than a permanent ileostomy. [28,29,30]. When discussing the treatment plan, we need to ensure that the patient understands all the possible consequences of a diverting stoma.…”
Section: Discussionmentioning
confidence: 99%